Reconstruction of historical 2, 3, 7, 8-tetrachlorodibenzo-p-dioxin discharges from a former pesticide manufacturing plant to the Lower Passaic River. (December 2018) - Parette, Robert; Velinsky, David J.; Pearson, Wendy N.
Abstract: Based on chemical fingerprinting and other lines of scientific evidence, a former pesticide manufacturing plant in Newark, New Jersey (U.S.A.) has been implicated in numerous journal articles as the major source of 2, 3, 7, 8-tetrachlorodibenzo- p -dioxin (TCDD) in the sediments of the Lower Passaic River (LPR). Although the site has been extensively studied for over three decades, no previous study has identified a pathway capable of discharging an amount of 2, 3, 7, 8-TCDD comparable to the mass estimates made for 2, 3, 7, 8-TCDD in the sediments of the LPR and Newark Bay, or examined the timing of specific manufacturing processes at the site in relation to 2, 3, 7, 8-TCDD concentrations in dated sediment cores. A reconstruction of the historical operations at this site was performed, supporting it as the major source of 2, 3, 7, 8-TCDD to the LPR. A 2, 4, 5-trichlorophenol purification process, utilized prior to September 1954, was specifically identified as a significant source of 2, 3, 7, 8-TCDD to the LPR. This purification process generated a dioxin-rich sludge that was discharged to the river prior to September 1954. Annual 2, 4, 5-trichlorophenol production, coupled with modeling to predict concentrations of 2, 3, 7, 8-TCDD, indicate that 2, 3, 7, 8-TCDD discharges to the LPR from this one process (20–80 kg) are consistent with mass estimates of 2, 3, 7, 8-TCDD in the river (30–50 kg). 2, 3, 7, 8-TCDD and cesium-137 data from nearby sediment cores support this purification process as a major pathway by which 2, 3, 7, 8-TCDD entered the river. Graphical abstract: Highlights: 2, 4, 5-TCP operations at a former pesticide plant in Newark, NJ, were reviewed. Waste sludge containing 2, 3, 7, 8-TCDD was discharged to Lower Passaic River (LPR). Estimated 2, 3, 7, 8-TCDD mass discharge is similar to mass of 2, 3, 7, 8-TCDD in the LPR. 2, 3, 7, 8-TCDD and Cs-137 sediment data support a major discharge pathway to the LPR. The findings supported this plant as the major source of 2, 3, 7, 8-TCDD to the LPR.